Keeping them in their place: the ambivalent relationship between development and migration in Africa - Bakewell, O (International Migration Institute, 2007)
Migration has moved to the centre stage of development policy after decades of waiting in the wings. For most of the last sixty years, migration has been portrayed in development circles in largely negative terms and identified as one of the problems that development aims to address in Africa. Suddenly in the last five years, the potential positive role of migration in the development process has been recognised – in particular the contribution of migrants through remittances, skills transfers, and the development of transnational networks. A virtuous circle has been identified, whereby migration supports economic growth and development and this in turn reduces the pressure for further migration. Researchers and policy makers are now hunting for conditions which make for a 'win-win-win’ situation where migration is beneficial for countries of origin, countries of settlement and the migrants themselves. Despite this apparent change in attitudes to migration, the vast majority of development agencies hold on to a sedentary model of development; they aim to enable people to achieve a better quality of life at 'home’; within such models continued migration is an indicator of failure. This sedentary bias is a reflection of the roots of the 'development project’ in Africa in the colonial administrations of twentieth century. Today, many of the new initiatives on migration and development have the implicit objective of reducing the flow of international migration, especially to the industrialised world. However, for many people in Africa increased opportunities for international migration (within and outside the continent) are an essential ingredient for their future well-being. Migration has always been a strategy used by people to try to improve their quality of life, and a development industry that fails to recognise this will severely limit its impact on poverty reduction.